Liberdade de expressão: a concepção integrada de Dworkin - LIMA, Sávio Barreto Lacerda (Universidade Federal do Pará, 2017)
To achieve the desired purpose of presenting Integrated right conception of freedom of expression in this research, the jus philosophical thought of Ronald Dworkin will be the starting point and main theoretical framework around the theme here exposed, given its understanding that ethics, morality, politics and law are integrated each other and propositions about the meaning of a value, a political ideal or a right should also support the other. Furthermore, it argues, still in favor of the possibility of assigning the status of objective truth to moral judgments - interpretative concepts in which the truth is revealed through the best argument which consensus is not guaranteed. In the study of freedom as political value developed in sequence, a brief historical overview of the evolution of the concept of freedom, important to show that, historically, freedom is understood as a fragmented value, highlighting in particular the thought of Benjamin Constant and Isaiah Berlin, philosophers of the modern era who wrote the most popular conceptions of freedom today. Also discuss an uncomfortable consequence of the fragmented conception of freedom, which places it in conflict with other important values such as it. Pursuing a conception of freedom based on the idea of the unity of value, grounded in Dworkin Moral Theory, which points to the need to justify the freedom by valid arguments also for other values will result in a conception of liberty sensitive to the meaning of other values, such as equality, with which they must reconcile rather than conflict. Subsequently, an approach to freedom as a right, dealing with the relationship between law and morality, and showing an understanding of human rights to demonstrate its alignment with the theory defended here. Will be sustained also the impossibility of speaking of a general right to freedom, concluding, as a result, it has, in fact, the right to various freedoms. And finally, it brings on the specific research point, the right to freedom of expression, expounding upon the understanding of the majority doctrine of that right as a fragmented value, to defend an integrated approach with other values and rights, by understanding that the right to freedom of expression, understood this way, reveals its true resource character to be distributed according to the distributive justice criteria. The best way to assimilate this right is by the integrity of the values held through the moral reading. To invigorate the arguments, the analysis of a case — HC 82 424 — which aroused great legal debate on the right to freedom of expression. The thesis is in favor of freedom of expression that reinforces what you think about other rights and to be strengthened by them.